Acu-TENS and Postexercise Expiratory Flow Volume in Healthy Subjects. (6th February 2011) - Ngai, Shirley P. C.; Jones, Alice Y. M.; Hui-Chan, Christina W. Y.
Abstract : Transcutaneous Electrical Nerve Stimulation over acupoints (Acu-TENS) facilitates recovery of resting heart rate after treadmill exercise in healthy subjects. Its effect on postexercise respiratory indices has not been reported. This study investigates the effect of Acu-TENS on forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) in healthy subjects after a submaximal exercise. Eleven male subjects were invited to the laboratory twice, two weeks apart, to receive in random order either Acu-TENS or Placebo-TENS (no electrical output from the TENS unit) over bilateral Lieque (LU7) and Dingchuan (EX-B1) for 45 minutes, before undergoing exercise following the Bruce protocol. Exercise duration, rate of perceived exertion (RPE), and peak heart rate (PHR) were recorded. Between-group FEV1 and FVC, before, immediately after, at 15, 30, and 45minutes postexercise, were compared. While no between-group differences in PHR, RPE, and FVC were found, Acu-TENS was associated with a longer exercise duration (0.9 min (P = .026 )) and a higher percentage increase in FEV1 at 15 and 45 minutes postexercise (3.3 ± 3.7% (P = .013 ) and 5.1 ± 7.5% (P = .047 ), resp.) compared to Placebo-TENS. We concluded that Acu-TENS was associated with a higher postexercise FEV1 and a prolongation of submaximal exercise.